2005
DOI: 10.2135/cropsci2004.0301
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Crosses among French and Spanish Maize Populations across Environments

Abstract: teristics such as early vigor, earliness, resistance to stem lodging, and relative resistance to drought stress. In Heterotic patterns among European maize (Zea mays L.) populaaddition, flint kernels possess a better potential than tions are strongly affected by genotype ϫ environment (GE) interacother kernels for developing high quality flours. Theretions and no single heterotic pattern has been identified so far that is not influenced by GE interaction. The objectives of this work fore, the high quality flou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
3
23
2
Order By: Relevance
“…In another study, the tion and grain-setting (Aylor, 2003). Similar results in other studies confirmed maximum daily temperatures (Malvar et al, 2005;Vargas et al, 2006) and average air humidity (Butron et al, 2004) to be important environmental factors that explain GEI component of grain yield.…”
supporting
confidence: 76%
“…In another study, the tion and grain-setting (Aylor, 2003). Similar results in other studies confirmed maximum daily temperatures (Malvar et al, 2005;Vargas et al, 2006) and average air humidity (Butron et al, 2004) to be important environmental factors that explain GEI component of grain yield.…”
supporting
confidence: 76%
“…Oroso is also the best potential donor of favourable alleles for sweetcorn survival under cold conditions . Another promising field corn population for improving the adaptation of sweetcorn to northern Spain is Lazcano; out of 12 flint corn populations it achieved the best yields across different locations in Spain and France (Malvar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lazcano performs well on both the northern Spanish coast and in the interior (Malvar et al, 2005). However, Rastrojero is well adapted to the conditions of Spain's interior and could be a promising source of adaptation traits for sweetcorn in this region; it could also help to improve sweetcorn resistance to corn borers (Malvar et al, 1993(Malvar et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yan et al (2001) ideal genotypes should have large projections of their markers towards the ASC abscissa to show high performance and small, preferably zero projection onto the ASC ordinate to show high stability of performance. Plant breeders and agronomists have found SREG biplot analysis to be useful for genotype evaluation (Butron et al 2004, Malvar et al 2005, Preciado-Ortiz et al 2006, Fan et al 2007.…”
Section: Resultsmentioning
confidence: 99%